The Influence of Clinical Placements on the Emotional Intelligence of Therapy Students - Gribble, Nigel Charles (Curtin University, 2019)
This research investigated changes in emotional intelligence (EI) in undergraduate speech, occupational and physical therapy students as they completed their final year of fieldwork. Undergraduate business students were a control group. The study used a longitudinal, mixed methods design measuring EI at three-points, with follow up interviews to explore reasons for changes in emotional intelligence. The study highlights the important role of clinical placements, reflective practice, and supervisor quality on the development of emotional intelligence.